Mechanism-based explanations and process tracing in communication: fundamentals and advantages - Fitz Herbert, Arturo Luis (2024)
Bunge (1997) argues that a good scientific explanation should detail the mechanisms that lead from causes to effects. In recent decades, this type of explanation has been incorporated into the dominant paradigms in sociology and political science, where it has achieved both theoretical and methodological advances, above all through the process tracing technique. In contrast, in communication there continues to be an almost exclusive dominance of theories and research using interpretive or variance methods. This paper argues that advances in the mechanism paradigm in other disciplines can be exploited by researchers in the field of communication who wish to study both classical issues in the discipline and social processes in which communication is involved as a relevant causal factor. The main definitions of the paradigm and the most important recommendations of the process tracing methodology are presented. Furthermore, Elizalde’s (2006) theory of the spiral of dissent is used to exemplify how these concepts and procedures can be empirically applied to a theory of the communication discipline.